2002
DOI: 10.1089/10906570260471804
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Genetic Testing in Patients At Risk for HNPCC/FAP and the German Population

Abstract: Adequate knowledge regarding hereditary diseases and genetics, as well as personal attitudes toward gene tests, are major determinants of optimal utilization of genetic testing. In the present study, we aimed to explore the general attitudes toward genetic testing in a sample representative of the German general population (n = 2,076) and to compare the attitudes of persons at risk for hereditary non-polyposis colorectal cancer/familial adenomatous polyposis (HNPCC/FAP) (n = 36) who had attended a university g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
4
18
0
4
Order By: Relevance
“…The result is in line with the findings of previous studies on genetic testing (albeit not specifically related to pharmacogenomics), indicating acceptance of genetic testing, particularly among patients who are ill or at-risk persons [13,14,15]. …”
Section: Discussionsupporting
confidence: 89%
“…The result is in line with the findings of previous studies on genetic testing (albeit not specifically related to pharmacogenomics), indicating acceptance of genetic testing, particularly among patients who are ill or at-risk persons [13,14,15]. …”
Section: Discussionsupporting
confidence: 89%
“…Such studies would facilitate adopting certain policies and performing the necessary steps that would expedite integration of genomics into healthcare. These studies, conducted in various countries in Europe and the US [3,4,5,6,7], have shown that the level of the general public's awareness of genomic medicine and its impact on society is often rather low, which constitutes a major barrier to expediting the implementation of genomic medicine. In addition, the lack of proper mapping of the opinions of various stakeholders leads to an inadequately regulated environment in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Barth et al [3,4] erfragten unter anderem die Einstellungen von Frauen aus der deutschen Allgemeinbevölkerung zu prädiktiver Gendiagnostik für somatische Erkrankungen im Erwachsenenalter: 47% der Frauen stimmten der Anwendung solcher Testungen zu, 40% lehnten diese ab. In Studien zur genetischen Diagnostik an repräsenta-tiven Stichproben in Finnland [2] und Deutschland [5] wurde insgesamt eher eine befürworten-de Haltung der Allgemeinbevölkerung zur genetischen Diagnostik gefunden. Die Befürwor-tung war in Deutschland geringer ausgeprägt als in Finnland.…”
Section: Einstellungen Zu Diagnostischen Verfahren In Der Medizinunclassified
“…Zwischen der Zentralität der Religiosität und der Befürwor-tung der Forschung mit Embryonen zeigt sich ebenfalls ein negativer Zusammenhang. Dies deckt sich mit Befunden aus der Allgemeinbevölkerung zum Einfluss der Religiosität auf Einstellungen gegenüber der Forschung mit Embryonen [28] und in Bezug auf andere ethisch umstrittene Themen, wie Abtreibung [0] oder Gentests [5].…”
Section: Einflussgrößen Auf Die Befürwortende Einstellung Zur Forschuunclassified